2012
DOI: 10.1038/pr.2012.64
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist improves patient–ventilator interaction in infants as compared with conventional ventilation

Abstract: Background: Neurally adjusted ventilatory assist (NaVa) is a mode of ventilation controlled by the electrical activity of the diaphragm (edi). The aim was to evaluate patient-ventilator interaction in infants during NaVa as compared with conventional ventilation. Methods: Infants were successively ventilated with NaVa, pressure control ventilation (PcV), and pressure support ventilation (PsV). edi and ventilator pressure (Pvent) waveforms were compared and their variability was assessed by coefficients of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
69
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 36 publications
11
69
0
1
Order By: Relevance
“…Additionally, this knowledge could be of major interest when comparing improved patient-ventilator synchrony documented with neurally adjusted ventilatory assist. 8,9 The purpose of this study was to investigate, using a bench model, the hypothesis that neonatal and/or adult ventilators equipped with neonatal/pediatric modes currently do not reliably administer pressure support (PS) in the absence or presence of air leaks.…”
Section: See the Related Editorial On Page 1606mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this knowledge could be of major interest when comparing improved patient-ventilator synchrony documented with neurally adjusted ventilatory assist. 8,9 The purpose of this study was to investigate, using a bench model, the hypothesis that neonatal and/or adult ventilators equipped with neonatal/pediatric modes currently do not reliably administer pressure support (PS) in the absence or presence of air leaks.…”
Section: See the Related Editorial On Page 1606mentioning
confidence: 99%
“…However, in our bench test, the trigger delays measured for the Servo-i were in line with the values reported in clinical settings. 8,9,24 Pressurization. In the pediatric literature, there are a striking lack of data on the possible clinical impact of pressurization capacities of mechanical ventilators.…”
Section: Ventilation Performance In the Absence Of Leaksmentioning
confidence: 99%
“…2 Adult and pediatric studies showed that NAVA increases breath-to-breath variability and improves patient-ventilator synchrony and patient comfort. [3][4][5][6][7][8][9] This last improvement is also effective in NIV in adult and pediatric subjects 10,11 and in very low birthweight infants, even in the presence of large leaks. 12 To our knowledge, no previous study was designed to evaluate this ventilation mode exclusively in the postoperative period after cardiac surgery in newborns.…”
Section: Introductionmentioning
confidence: 96%
“…Compared with adults, children have a relatively higher breathing frequency, which can adversely affect patient-ventilator synchrony during PSV. 11,12 However, ventilator settings and interfaces used affect patient-ventilator synchrony in both cases. 13 Although neurally adjusted ventilatory assist (NAVA) has been proposed as a partial ventilatory support mode to improve patient-ventilator synchrony, 11,14,15 its use has been limited by the elevated cost of the catheter and need for specific equipment.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, ventilator settings and interfaces used affect patient-ventilator synchrony in both cases. 13 Although neurally adjusted ventilatory assist (NAVA) has been proposed as a partial ventilatory support mode to improve patient-ventilator synchrony, 11,14,15 its use has been limited by the elevated cost of the catheter and need for specific equipment. Therefore, PSV still remains, in most adult and pediatric ICUs, the accepted standard for delivering partial ventilatory support during invasive and noninvasive ventilation.…”
Section: Introductionmentioning
confidence: 99%